Turbot Survivability, Catches and Gillnet-Caused Injuries. Scientific Support for the Exemption from the Landing Obligation in EU Black Sea Countries - Niță, Victor; Nenciu, Magda; Danilov, Cristian; Țiganov, George; Galațchi, Mădălina; Păun, Cătălin; Diaconu, Dragoș; Grigoraș, Daniel (Cercetări Marine - Recherches Marines, 2022)
The European Common Fisheries Policy aims to gradually eliminate discards in all European Union fisheries through the introduction of a landing obligation for all catches of species subject to catch limits (turbot and sprat for the Black Sea). In 2016, the Commission established a discard plan for turbot fisheries in the Black Sea, that provided for a survivability exemption of turbot caught with bottom-set gillnets, applied from 1 January 2017 until 31 December 2019. Subsequently, Romania and Bulgaria submitted an updated Joint Recommendation to the Commission, requesting the renewal of the discard plan and the survivability exemption based on the high survival rates of this species. The Scientific, Technical and Economic Committee for Fisheries (STECF) acknowledged the existence of data demonstrating the high survivability of turbot caught by vessels from non-EU countries using the same gears, however they requested that Member States concerned should submit additional data on survival estimates relating to the gillnet fishery for turbot. In this context, NIMRD “Grigore Antipa“ was commissioned by the Romanian National Agency for Fisheries and Aquaculture (NAFA) to perform a pilot study aiming at obtaining scientific evidence for the exemption of turbot from the landing obligation, carried-out during January-April 2022. Scientific fishing was performed in the Romanian marine area with specialized gears - turbot gillnets on board of NIMRD’s boat. The methodology consisted of launching the gillnets in established locations and recovering them after a soaking time depending on weather conditions. After each operation to recover the nets from the water, all turbot specimens caught were retained on board, parked in a fiber-reinforced polymer (FRP) container filled with seawater and equipped with an aeration system. The specimens were kept in the tank for 1 hour, during which time they were monitored from the point of view of their condition (dead, alive, injuries, other negative effects produced by the fishing gear). Subsequently, all turbot specimens declared viable were released back into the sea. The results indicate high survivability rates of turbot caught in gillnets (81.67%). Some injuries were reported in the dead specimens, probably caused by the mechanical action of the gear.